PECULIARITIES OF DIAGNOSIS AND CLINICAL PICTURE OF POSTTRAUMATIC EPILEPSY AGAINST THE BACKGROUND OF CONCOMITANT SOMATIC DISEASES - Khudaynazarova Muattar Tokhirjonovna; Ruziyev Jononbek Elmurodovich; Kasimov Arslanbek Atabayevich (Scholar Express Journals, 2022)
Diseases of CNS are most susceptible to the aging processes due to regenerative features of nerve cells. There are significant clinical and neurological peculiarities of motor skills, coordination, sensitivity, higher mental functions and brain electrogenesis. Changes in higher nervous activity in the form of weakening of inhibitory and excitatory processes, disturbance of their equilibrium, weakening of cortical tone, changes in emotional sphere lead to memory disturbance and appearance or strengthening of inadequate speech and behavioral reactions, changes in locomotor sphere.
Keywords: epilepsy; Binswanger's encephalopathies; dementia; CNS